Improving crop resilience to salinity stress using growth regulators - Soni, Pooja Gupta; Roohi; Kannoj; kamboj, Paras; Rani, Sarita; Satpal; Kumar, Krishan (Indian Farming, 2025)
Worldwide climate change and declining availability of high-quality water lead to an increase in the salinization of agricultural lands. One of the major abiotic factors limiting plant growth and development is soil salinity. High salts concentrations in soil and water interfere plant physiological and metabolic processes, ultimately resulting in reduced growth, quality, and yield. In recent years, the application of plant growth regulators (Exogenous application or seed priming) can enhance plant tolerance to stress by modifying ionic and redox homeostasis, enhancing antioxidant activity, and affecting stress-responsive gene expression. Growth regulators such as abscisic acid, salicylic acid, jasmonic acid, gibberellins, cytokinins, and ethylene play an important role in reducing the harmful effects of salinity on plant growth and yield.